Implementasi Personal Assistant Library Service (PALS) dalam meningkatkan layanan referensi di perpustakaan perguruan tinggi - Febriyanto Febriyanto; Tamara Adriani Salim (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. The academic library in the Pancoran area have user-oriented reference services by creating services called Personal Assistant Library Service (PALS). This paper discusses the reference services at Pancoran University which aims to describe the implementation of PALS at Universitas Pancoran as an effort to improve the academic library. Method. The method uses case study with qualitative approach. Techniques of collecting data through interviews conducted on librarians who work in the library. Results and Discussions. The findings of the strategy undertaken in an effort to improve reference services at the Pancoran University library can be done in a personal way by forming PALS services. In the case of Pancoran University, these efforts are reflected in the collection support provided for new services, reassessing the competencies needed for services and seeing the challenges that exist in its implementation. Conclusion. The improvement of college library services through PALS is an alternative that can be used by other university libraries even though the application at Pancoran University has not been maximized. PALS focuses on the needs of college library users with high ability needs and different subjects with personal handling.